Modulation of biological activities in adipose derived stem cells by histone deacetylation - Sallam Abdallah; Mouna Tabebi; Sawsan Qanadilo; Neserin Ali; Jing Wang; Pádraig D’Arcy; Wen Zhong; Folke Sjoberg; Moustafa Elmasry; Ahmed El-Serafi (Scientific Reports)
Abstract Difficult-to-heal wounds management accounts for about 4% of healthcare costs, highlighting the need for innovative solutions. Extracellular signals drive cell proliferation during tissue regeneration, while epigenetic mechanisms regulate stem cell homeostasis, differentiation, and skin repair. Exploring epigenetic regulation in adipose-derived stem cells (ADSCs) holds promise for improving skin injury treatments. We investigated the effects of histone deacetylase inhibitor (SAHA) on ADSCs to better understand its cellular and molecular impacts. ADSCs were treated with SAHA for 72 h, showing no change in cell viability at the studied concentrations. However, the expression of histone deacetylase decreased at 1000 nM, while the cell proliferation marker Ki-67 increased after SAHA treatment, as confirmed by immunofluorescence. CCND1 gene expression increased, whereas protein expression of the proliferating cell nuclear antigen (PCNA) decreased. Cell cycle analysis showed an increase in G2 phase in SAHA-treated cells. Microarray analysis revealed 74 upregulated and 40 downregulated differentially expressed genes, including upregulation of P53 targets, CDKN1A and MDM2. Proteomic analysis identified 631 upregulated and 823 downregulated proteins compared to the vehicle. Pathway enrichment analysis showed cell cycle, ATP-dependent chromatin remodeling and DNA processes were among the affected pathways. This study suggests SAHA modulates ADSCs’ biological processes, highlighting its potential for skin regeneration.